2005
DOI: 10.1093/ejo/cji040
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary canine anomalies and tooth agenesis

Abstract: The aims of the study were to analyse the records of 26 subjects (18 females, eight males) with maxillary canine-first premolar transposition (Mx.C.P1) together with 160 subjects with a palatally displaced canine (PDC) to determine the pattern of tooth agenesis in these cases and to compare them with similar samples reported in the literature. A strong association between Mx.C.P1, lateral incisor and lower second premolar agenesis was found, with a 20 per cent prevalence of lateral incisor agenesis and a 24 pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
3
9

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 26 publications
0
27
3
9
Order By: Relevance
“…14 The PDCG showed a relatively high prevalence of peg-shaped maxillary lateral incisors (10.5%) compared to the CG (2%); in fact, a statistically significant association was verified, as previously reported. 4,7,8,11,14,20,22,24,27 Different authors have also related transposition to PDCs 16,18,19 ; the present PDCG presented some cases of concomitant transposition, and a statistically significant association was found. However, this study did not confirm the association of BDCs with impaction of other teeth.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…14 The PDCG showed a relatively high prevalence of peg-shaped maxillary lateral incisors (10.5%) compared to the CG (2%); in fact, a statistically significant association was verified, as previously reported. 4,7,8,11,14,20,22,24,27 Different authors have also related transposition to PDCs 16,18,19 ; the present PDCG presented some cases of concomitant transposition, and a statistically significant association was found. However, this study did not confirm the association of BDCs with impaction of other teeth.…”
Section: Discussionmentioning
confidence: 53%
“…In spite of these considerations, a great number of studies suggested the ''genetic theory'' 4 of PDCs: given the simultaneous occurrence of PDCs and congenital dental anomalies, these authors believed that a PDC was only one aspect of a general dental eruption disorder that could be genetic in origin. [12][13][14][15][16][17][18][19][20][21] Evidence has been mounting regarding the association of PDCs with congenital missing teeth 4,12 ; in particular, associations with maxillary lateral incisor 1,3,12,14 and second premolar 17 aplasia have been observed. Numerous studies have highlighted the association between PDCs and tooth size reduction, especially of the maxillary lateral incisor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mesiodistal crown width of the maxillary and mandibular incisors have been reported to be significantly smaller in patients with palatal canine impaction. 1,[4][5][6][7]10,11,12,14 The root length of lateral incisors adjacent to palatally displaced canines was also reported as responsible for the displacement of the palatally impacted maxillary canines. 8 To correct this malocclusion, the most common preventive treatment is to extract the deciduous canine expecting that the permanent canine will adjust its position by itself.…”
Section: Introductionmentioning
confidence: 99%
“…The displacement of the crypt, long path of eruption, short-rooted or absent upper lateral incisor, crowding, retention of the primary deciduous canine, and genetic factors have been suggested as causative factors of eruption disturbances. 5,6 The ectopic maxillary ca- nine is located palatally to the dental arch in about 85% and buccally in only about 15% of the cases. 7 It has been reported that buccal displacement is most frequently associated with crowding, 8 whereas most palatal canine displacements occur in dentitions without crowding.…”
Section: Introductionmentioning
confidence: 99%